A TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing carbon dioxide to generate methane and a preparation method and application thereof

CN122974362APending Publication Date: 2026-10-27YANTAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611452069.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有技术中已有少量关于COF与金属硫化物复合光催化剂的研究,但是由于COF材料的问题,其与金属硫化物组成的复合光催化材料大多是简单的混合或负载,异质结界面的结合性差,只能得到CO

Benefits of technology

1.根据本申请的TAPB-DMTP-COF@ZnIn2S4复合光催化剂,通过调控TAPB-DMTP-COF质量分数在0.1%~1.0wt%范围内,可以促进ZnIn2S4的均匀分散,能够提升界面结合力、壳层包覆的完整性、TAPB-DMTP-COF@ZnIn2S4结构的均匀性、CH4选择性和稳定性,可实现光吸收、载流子分离与表面活性的精准匹配,便于批量制备与性能稳定控制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974362A_ABST
    Figure CN122974362A_ABST
Patent Text Reader

Abstract

The application discloses a TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing carbon dioxide to generate methane and a preparation method and application thereof, and belongs to the technical field of energy and environmental catalytic materials. The composite photocatalyst is of a core-shell structure, ZnIn2S4 is coated on the TAPB-DMTP-COF inner core by means of in-situ growth coating, the interface charge transfer impedance is significantly reduced, the photo-generated carrier separation and migration are accelerated, and the electron-hole recombination is inhibited, so that CO2 can be reduced to CH4, and the photocatalytic rate can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing the production of methane from carbon dioxide, its preparation method and application, belonging to the field of energy and environmental catalytic materials technology. Background Technology

[0002] Currently, the continuous rise in carbon dioxide (CO2) emissions has led to a series of environmental and energy problems, including the greenhouse effect, global warming, and frequent extreme weather events. The priority strategies for addressing this change are source reduction and replacing fossil fuels with wind, solar, and hydropower. However, considering the massive global emissions and the existence of some energy-intensive industries that are difficult to electrify, the resource utilization of CO2, particularly its selective conversion into high-value-added carbon-based fuels or chemicals such as methane (CH4), carbon monoxide (CO), and methanol—products with high energy density and well-developed storage and transportation infrastructure—has become a research hotspot in the field of CO2 capture and utilization. CH4, as the main component of natural gas with the highest added value, is the most ideal reduction product of CO2. However, the reduction of CO2 to CO is a two-electron reduction process, while the reduction of CO2 to CH4 is an eight-electron reduction process, meaning that the reduction of CO2 to CH4 requires significantly more energy.

[0003] Photocatalysis, as a green and efficient reaction technology, is considered one of the most promising strategies for CO2 to CH4 reduction. However, the practical application of photocatalytic CO2 reduction is limited by the properties of the catalyst itself, resulting in key scientific and technological problems such as low visible light utilization, rapid recombination rate of photogenerated carriers, poor reaction selectivity, and unsatisfactory stability. Therefore, developing novel photocatalytic materials with high activity, high selectivity, and high stability is of great significance for promoting the industrial application of photocatalytic CO2 to CH4 reduction technology.

[0004] Zinc indium sulfide (ZnIn2S4) is a typical ternary chalcogenide semiconductor with a suitable reduction potential, meeting the thermodynamic requirements for the reduction of CO2 to CH4. However, single ZnIn2S4 exhibits drawbacks during use, including easy recombination of photogenerated carriers, low charge separation and migration efficiency, and slow surface reaction kinetics. These limitations make its photocatalytic CO2 reduction activity and CH4 selectivity insufficient for practical applications. Furthermore, single ZnIn2S4 readily aggregates in solution, significantly impacting the reduction efficiency.

[0005] Covalent organic frameworks (COFs) are a class of crystalline porous organic polymers formed by covalently linked organic structural units. They possess significant advantages such as large specific surface area, regular and ordered pore structure, precise design of structure and function, tunable band structure, and abundant active sites, demonstrating great potential in the field of photocatalysis. Existing technologies have yielded some research on COF-metal sulfide composite photocatalysts. However, due to limitations of COF materials, most of these composite photocatalysts are simple mixtures or supports, exhibiting poor bonding at the heterojunction interface and only yielding CO. For example, CN118904396A discloses a method for preparing a core-shell structured COF-ZnIn2S4 photocatalyst. This photocatalyst can only reduce CO2 to CO, not to CH4, which requires higher photoexcitation energy. Furthermore, it suffers from difficulties in promoting ZnIn2S4 dispersion, resulting in weak catalytic interface bonding, poor structural controllability, incomplete shell coating, limited activity enhancement, low CH4 selectivity, and insufficient stability.

[0006] Therefore, developing a composite photocatalyst with controllable structure, tight interface, high activity, strong selectivity, good stability, and the ability to catalyze the production of methane from carbon dioxide has significant scientific value and application prospects. Summary of the Invention

[0007] To address the aforementioned issues, a method for developing a TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing the conversion of carbon dioxide to methane is provided. This composite photocatalyst, constructed through in-situ growth of a complete encapsulated core-shell heterostructure, is capable of reducing CO2 to CH4 with a yield greater than 10.0 µmol g. -1 h -1 .

[0008] This application provides a TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing the production of methane from carbon dioxide. The composite photocatalyst has a core-shell structure, wherein TAPB-DMTP-COF is the core and ZnIn2S4 is the shell. The ZnIn2S4 shell is grown in situ on the surface of the TAPB-DMTP-COF core and coats the surface of the TAPB-DMTP-COF core. The composite photocatalyst has a CH4 yield greater than 10.0 µmol g. -1 h -1 .

[0009] This application reveals that while TAPB-DMTP-COF belongs to the category of COF materials, it suffers from problems such as low separation efficiency of photogenerated electron-hole pairs, severe carrier recombination, and limited intrinsic catalytic activity. The composite photocatalyst prepared in this application combines TAPB-DMTP-COF with ZnIn2S4, which not only solves the problem of insufficient photocatalytic energy in a single TAPB-DMTP-COF structure but also addresses the issues of poor structural controllability, limited activity enhancement, low CH4 selectivity, and insufficient stability caused by the aggregation of ZnIn2S4 when used alone.

[0010] In addition, the in-situ growth method enables a strong chemical interface bond between the TAPB-DMTP-COF core and the ZnIn2S4 shell, thus making it less prone to shell shedding and phase separation during the photocatalytic reaction, thereby improving carrier separation efficiency and significantly increasing catalyst lifetime.

[0011] Optionally, the mass fraction of the TAPB-DMTP-COF core in the composite photocatalyst is 0.1% to 1.0 wt%.

[0012] The ratio of TAPB-DMTP-COF to ZnIn2S4 directly affects the uniformity and integrity of the core-shell structure, the bonding performance of the heterojunction interface, the photogenerated carrier separation efficiency, and the dispersion uniformity of ZnIn2S4, thus significantly impacting the catalytic performance of the photocatalyst. A low TAPB-DMTP-COF mass fraction leads to insufficient heterojunction interfaces, hindering effective charge separation and limiting catalytic activity improvement. It also results in uneven ZnIn2S4 dispersion, causing aggregation of single-component ZnIn2S4 or the generated TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst, reducing photocatalytic stability and reaction efficiency. Conversely, a high TAPB-DMTP-COF mass fraction leads to discontinuous ZnIn2S4 shell growth and incomplete coating. Excessive TAPB-DMTP-COF also tends to become a carrier recombination center, reducing light absorption and catalytic reaction efficiency.

[0013] Preferably, the mass fraction of the TAPB-DMTP-COF core in the composite photocatalyst is 0.5 wt%.

[0014] Optionally, the average particle size of the TAPB-DMTP-COF core is 400-490 nm, and the average thickness of the ZnIn2S4 shell is 300-335 nm.

[0015] The core particle size of TAPB-DMTP-COF affects the dispersibility, specific surface area, and shell coating uniformity of the composite photocatalyst, thus impacting the overall performance of the photocatalyst. If the particle size is too small, the particles are prone to agglomeration, reducing the dispersion of ZnIn2S4 and leading to uneven ZnIn2S4 shell coating. If the particle size is too large, the specific surface area is significantly reduced, decreasing the number of exposed active sites, which is detrimental to CO2 adsorption and activation, thus failing to improve CH4 yield or even prevent CH4 formation.

[0016] The shell thickness affects light absorption efficiency, carrier migration distance, and structural stability, thus impacting photocatalytic performance. If the shell is too thin, it cannot effectively encapsulate the TAPB-DMTP-COF core, resulting in insufficient interfacial contact. If the shell is too thick, it increases the migration path of photogenerated carriers, making electron-hole recombination more likely, while also generating a light shielding effect and reducing visible light utilization.

[0017] Optionally, the CO2 chemisorption capacity of the composite photocatalyst is not less than 19 μmol g. -1 .

[0018] The CO2 chemisorption capacity of the composite photocatalyst is calculated using the following formula:

[0019] Optionally, the composite photocatalyst has a selectivity of not less than 99.0% for CH4.

[0020] The CH4 selectivity of the composite photocatalyst is calculated using the following formula:

[0021] Where Y represents the generation rate; The composite photocatalyst exhibits an absorption edge redshift to the 790-810 nm range in the UV-Vis diffuse reflectance spectrum.

[0022] In existing technologies, the UV-Vis diffuse reflectance absorption edges of ZnIn2S4-based composite photocatalysts are mostly in the 530–650 nm range; even when using TAPB-type COFs to construct core-shell heterojunctions, the highest absorption edge is only about 750 nm. This redshift of the absorption edges indicates that the composite photocatalyst broadens the visible light response range and improves solar energy utilization. If the redshift is not significant, it suggests a weak composite effect, with no effective synergistic effect between the two components, thus failing to improve the efficiency of CO2 reduction to CH4.

[0023] The composite photocatalyst maintained stable catalytic performance in four consecutive cycles, with a CH4 precipitation rate remaining at 50 μmol g / L during these cycles, conducted at 2-hour intervals. -1 h-1 The selectivity of CH4 remains above 95%.

[0024] The stability showed no significant decline and was strong, confirming that the photocatalyst has a stable structure and that the active sites can maintain their activity for a long time during the reaction, enabling it to operate efficiently for a long period of time.

[0025] According to a second aspect of this application, a method for preparing the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst as described in any one of the above claims is provided, comprising the following steps: (1) Preparation of TAPB-DMTP-COF kernel; (2) The TAPB-DMTP-COF core is dispersed in a mixed solvent of glycerol and deionized water to obtain a mixed solution; (3) Add zinc acetate dihydrate, indium chloride tetrahydrate and thioacetamide to the mixture in step (2); (4) Heating causes ZnIn2S4 to grow in situ and coat the surface of the TAPB-DMTP-COF core. The composite photocatalyst is obtained by separation, washing and drying.

[0026] In step (1), the preparation method of the TAPB-DMTP-COF core is as follows: S1: Dissolve 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 2,5-dimethoxytetraphenylethylene (DMTP) in acetonitrile, add acetic acid solution, stir for 2-10 min to obtain a suspension, and let the suspension stand at room temperature for 72 h; S2: Separate the suspension from the reaction in step S1 to obtain a solid, and wash and dry the solid to obtain the final product.

[0027] Optionally, in step S1, acetic acid is added to provide an acidic environment for the system, promoting the Schiff base condensation reaction. The amount of acetic acid used directly affects the nucleation rate, crystallinity, and morphology of TAPB-DMTP-COF.

[0028] Optionally, the molar ratio of TAPB to acetic acid is 1:90.

[0029] If too little acetic acid is used, the condensation reaction will not proceed sufficiently, resulting in TAPB-DMTP-COF with low crystallinity and irregular morphology. If too much acetic acid is used, it will destroy the dynamic covalent bonds of the covalent organic framework, leading to the collapse of the framework and a significant decrease in specific surface area.

[0030] Optionally, the volume ratio of glycerol to deionized water in step (2) is 1:(2-4); preferably, the volume ratio of glycerol to deionized water is 1:3.

[0031] The ratio of glycerol to water affects the viscosity, surface tension, and dispersion state of TAPB-DMTP-COF, thus affecting the uniformity of the ZnIn2S4 shell. If the glycerol ratio is too high, the system viscosity will be too high, hindering the diffusion of zinc and indium, which can easily lead to local deposition and uneven coating. If the glycerol ratio is too low, the TAPB-DMTP-COF core will easily settle and agglomerate, failing to form a complete core-shell structure. In addition, the glycerol and deionized water system mentioned in step (2) is also the solvent in step (3). Using a good solvent common to both steps (2) and (3) can make TAPB-DMTP-COF premixed uniformly, resulting in a uniform particle size of the prepared composite photocatalyst, making it less prone to agglomeration, constructing a tightly contacted core-shell heterogeneous interface, promoting effective separation of photogenerated carriers, and improving the photocatalytic CO2 reduction performance.

[0032] Preferably, the volume ratio of glycerol to deionized water in step (2) is 1:3.

[0033] Optionally, the molar ratio of zinc acetate dihydrate, indium chloride tetrahydrate and thioacetamide in step (3) is 1:2:4.

[0034] The molar ratio of raw materials directly affects the phase purity, crystal structure, and morphology of ZnIn2S4. If the ratio of zinc, indium, and sulfur is imbalanced, impurity phases are easily generated, reducing crystallinity, altering the band structure, leading to a decrease in carrier separation efficiency and a significant reduction in photocatalytic performance.

[0035] Preferably, the reaction temperature in step (4) is 95°C and the reaction time is 2 h.

[0036] Reaction temperature and time affect the decomposition rate of thioacetamide, the crystallinity of ZnIn2S4, and the shell growth state. If the temperature is too low or the time is too short, ZnIn2S4 crystals will be poor and the shell growth will be discontinuous; if the temperature is too high or the time is too long, ZnIn2S4 nanosheets will grow excessively, their thickness will increase, and their specific surface area will decrease. At the same time, the core structure of TAPB-DMTP-COF may be destroyed.

[0037] Optionally, the washing method described in step (4) is washing three times with deionized water and three times with ethanol. Thorough washing can remove residual metal ions, anions, and organic impurities. If the washing is not thorough, residual impurities will cover the active sites, increase interfacial impedance, and reduce the separation and migration efficiency of photogenerated carriers.

[0038] According to a third aspect of this application, the application of the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst described in any of the above claims in the photocatalytic reduction of CO2 to CH4 is provided.

[0039] The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst described in this application, used to catalyze the production of methane from carbon dioxide, is a photocatalyst that, under visible light conditions, incorporates a photosensitizer and a sacrificial agent to carry out the catalytic reaction.

[0040] Optionally, the mass ratio of the composite photocatalyst, photosensitizer, and sacrificial agent is 1:1:339.

[0041] Preferably, the catalytic reaction uses visible light with λ≥420nm as the light source. Using visible light is closer to the actual solar spectrum, improving solar energy utilization; if it relies on ultraviolet light, the energy consumption is high, the safety is low, the equipment cost is high, and it is difficult to apply on a large scale.

[0042] Optionally, triethanolamine is added as a sacrificial agent in the catalytic reaction. The sacrificial agent can rapidly consume photogenerated holes and suppress electron-hole recombination. Without the addition of a sacrificial agent, carrier recombination is severe, quantum efficiency drops sharply, and CO2 reduction is almost impossible.

[0043] Optionally, ruthenium chloride hexahydrate is added as a photosensitizer in the catalytic reaction. As a classic metal complex photosensitizer, ruthenium chloride hexahydrate can efficiently absorb visible light and generate a long-lived excited state. It injects photogenerated electrons into the catalyst through an electron transfer process, significantly improving the quantum efficiency of the photocatalytic reaction. If the amount of photosensitizer is too small, light absorption and charge injection will be insufficient, making it difficult to effectively improve catalytic activity; if the amount is too large, a severe light-shielding effect will occur, hindering the catalyst's absorption of incident light and increasing the cost of the reaction system. Optionally, the reaction solvent is a mixture of water and acetonitrile. Acetonitrile can significantly increase the solubility of CO2 in the reaction system and enhance substrate mass transfer. If only water is used as the solvent, the solubility of CO2 is low, and the reaction rate is slow; if the proportion of acetonitrile is too high, it will reduce the polarity of the system and affect the charge transfer efficiency.

[0044] Optionally, the system is purged with high-purity CO2 for 20 min before the catalytic reaction. Thorough purging completely removes air from the system, preventing interference from O2, N2, and other substances that could cause side reactions. Insufficient purging will result in residual O2 and N2 competing for photogenerated electrons, leading to a significant decrease in CH4 yield and selectivity.

[0045] Based on the application of the aforementioned TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst in the photocatalytic reduction of CO2 to CH4, the CH4 yield of the composite photocatalyst is greater than 10.0 µmol g- 1 h -1 .

[0046] The beneficial effects of this application include, but are not limited to: 1. The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst of this application can promote the uniform dispersion of ZnIn2S4 by adjusting the mass fraction of TAPB-DMTP-COF in the range of 0.1%~1.0wt%, thereby improving the interfacial bonding force, the integrity of the shell coating, the uniformity of the TAPB-DMTP-COF@ZnIn2S4 structure, CH4 selectivity and stability. It can achieve precise matching of light absorption, carrier separation and surface activity, which is convenient for batch preparation and stable performance control.

[0047] 2. The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst of this application adopts the in-situ growth and coating process of ZnIn2S4, which can achieve precise matching of light absorption, carrier separation and surface activity, significantly reduce the interfacial charge transfer impedance, accelerate the separation and migration of photogenerated carriers, and suppress electron-hole recombination, thereby improving the efficiency of photocatalytic reaction.

[0048] 3. The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst of this application adopts a fully encapsulated core-shell structure design, in which the ZnIn2S4 shell layer is coated on the surface of the TAPB-DMTP-COF core, which can provide more efficient heterojunction interfaces, significantly enhance structural stability, improve photocatalytic reaction activity and CH4 selectivity, and thus exhibit excellent photocatalytic CO2 reduction to CH4 performance.

[0049] 4. The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst of this application exhibits high activity, high selectivity, and high stability under visible light, with a CH4 yield of up to 59.3 µmol g. -1 h -1 With a selectivity of up to 99.0%, the activity was 4.9 times that of the pure TAPB-DMTP-COF core and 3.5 times that of the pure ZnIn2S4. In the stability test of four consecutive cycles (2 h each time), the CH4 yield did not decrease significantly, and the structure and morphology remained intact, demonstrating excellent reusability and high catalytic activity.

[0050] 5. The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst of this application can achieve efficient and selective reduction of CO2 to CH4 at room temperature and pressure, converting greenhouse gases into clean energy. It has significant application value and broad prospects in the fields of photocatalysis, environmental remediation and solar fuels. Attached Figure Description

[0051] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 The total CO2 adsorption spectroscopy of TAPB-DMTP-COF@ZnIn2S4, TAPB-DMTP-COF, and ZnIn2S4 prepared in Example 1, Comparative Example 1, and Comparative Example 2 is shown.

[0052] Figure 2 Cyclic performance spectrum of TAPB-DMTP-COF@ZnIn2S4 prepared in Example 1.

[0053] Figure 3 Photocurrent spectra of TAPB-DMTP-COF@ZnIn2S4, TAPB-DMTP-COF, and ZnIn2S4 prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0054] Figure 4 Impedance spectra of TAPB-DMTP-COF@ZnIn2S4, TAPB-DMTP-COF, and ZnIn2S4 prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0055] Figure 5 The fluorescence lifetime spectra of TAPB-DMTP-COF@ZnIn2S4 (0.5COFZIS), TAPB-DMTP-COF (COF), and ZnIn2S4 (ZIS) prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Detailed Implementation

[0056] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0057] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0058] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0059] Example 1 This embodiment relates to a method for preparing a TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst, including the following steps: The preparation of composite photocatalysts includes the following steps: (1) Preparation of TAPB-DMTP-COF kernel: S1: Add 105.4 mg TAPB and 87.4 mg DMTP to 37.5 mL acetonitrile and stir until completely dissolved; add 2.25 mL 12 M acetic acid to the solution and stir rapidly to obtain a suspension; allow the suspension to stand at room temperature for 72 h. S2: After the reaction in step S1, the suspension was centrifuged at 10,000 rpm for 5 min, washed three times each with N,N-dimethylformamide, tetrahydrofuran, and ethanol, and the solid was collected. The solid was then dried under vacuum at 60℃ for 12 h to obtain the yellow TAPB-DMTP-COF core.

[0060] (2) Disperse 1.2 mg TAPB-DMTP-COF kernel in 60 mL of a mixed solvent of glycerol and water (volume ratio 1:3), and sonicate for 30 min to obtain a uniformly dispersed mixture; (3) Add 219.5 mg zinc acetate dihydrate and 586.5 mg indium chloride tetrahydrate to the mixture in step (2) and stir for 30 min; add 300.5 mg thioacetamide and continue stirring for 30 min; (4) Heat to 95℃ for 2 h, cool to room temperature, filter, wash 3 times each with deionized water and ethanol; dry under vacuum at 60℃ for 12 h to obtain TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst.

[0061] The photocatalytic CO2 reduction performance and cycle test of this composite photocatalyst were conducted as follows: The photocatalytic reaction was carried out in a sealed, temperature-controlled reactor at 20 °C using a 300 W xenon lamp (Perfect Light PLS-SXE300D) equipped with a 420 nm cutoff filter. The photocatalytic reduction of carbon dioxide was investigated. 10 mg of catalyst and 10 mg of triruthenium chloride hexahydrate were dispersed in 20 mL of a solution (15 mL water + 5 mL acetonitrile) and 3 mL triethanolamine, and the dispersion was performed by ultrasonication. To remove residual air, high-purity CO2 was introduced into the system, and the CO2 was vented for 20 min. Throughout the reaction, a condenser was used to maintain a constant temperature (20 °C) within the reactor. Every 1 h, 0.3 mL of the reaction gas was collected and quantitatively analyzed using a gas chromatograph equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD), for a total of two measurements.

[0062] Example 2 The difference between this embodiment and Embodiment 1 is that the amount of TAPB-DMTP-COF added is 0.24 mg, while the other steps are the same.

[0063] Example 3 The difference between this embodiment and Embodiment 1 is that the amount of TAPB-DMTP-COF added is 0.6 mg, while the other steps are the same.

[0064] Example 4 The difference between this embodiment and Embodiment 1 is that the amount of TAPB-DMTP-COF added is 2.4 mg, while the other steps are the same.

[0065] Example 5 The difference between this embodiment and embodiment 1 is that in step (4), the reaction is heated to 95°C for 2.5 h, while the other steps are the same.

[0066] Example 6 The difference between this embodiment and embodiment 1 is that in step (4), the reaction is heated to 95°C for 3 hours, while the other steps are the same.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is that the composite photocatalyst is replaced by the TAPB-DMTP-COF core prepared in step (1) of Example 1.

[0068] Comparative Example 2 The difference between this comparative example and Example 1 is that pure ZnIn2S4 is used to replace the composite photocatalyst. The preparation method of pure ZnIn2S4 includes the following steps: 219.5 mg of zinc acetate dihydrate and 586.5 mg of indium chloride tetrahydrate were dispersed in a 60 mL mixture of glycerol and water (volume ratio 1:3) and stirred for 1 h. 300.5 mg of thioacetamide was added and stirring was continued for 30 min. The mixture was reacted in an oil bath at 95 °C for 2 h. After cooling to room temperature, the mixture was filtered and washed three times each with deionized water and ethanol. The mixture was then dried under vacuum at 60 °C for 12 h to obtain orange-yellow ZnIn2S4 powder.

[0069] Comparative Example 3 The difference between this comparative example and Example 1 is that 10 mg of ruthenium chloride hexahydrate was not added when testing the photocatalytic CO2 reduction performance; the other steps were the same.

[0070] Comparative Example 4 The difference between this comparative example and Example 1 is that 3 mL of triethanolamine was not added when testing the photocatalytic CO2 reduction performance; the other steps were the same.

[0071] Comparative Example 5 The difference between this comparative example and Example 1 is that CO2 was not added (Ar was used instead) when testing the photocatalytic CO2 reduction performance; the other steps were the same.

[0072] Comparative Example 6 The difference between this comparative example and Example 1 is that the photocatalytic CO2 reduction performance test was performed without adding the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst prepared in Example 1; the other steps were the same.

[0073] Comparative Example 7 The difference between this comparative example and Example 1 is that the catalytic CO2 reduction performance test was conducted in a dark environment, while the other steps were the same.

[0074] Comparative Example 8 The difference between this comparative example and Example 1 is that in step (4), the mixture is heated to 100°C and reacted for 2 hours, while the other steps are the same.

[0075] Test Example 1 The photocatalysts prepared in the above embodiments and comparative examples and the test results of their photocatalytic performance are detailed in Table 1.

[0076] Table 1

[0077] Based on the above test results, the CH4 production rate of CO2 reduction by this photocatalyst gradually increases with the increase of the TAPB-DMTP-COF mass fraction from 0 to 0.5%, reaching a maximum value of 59.3 µmol g when the TAPB-DMTP-COF mass fraction is 0.5%. -1 h -1 When the mass fraction of TAPB-DMTP-COF continued to increase to 1.0%, the CH4 precipitation rate actually decreased to 20.9 µmol g. -1 h -1 This indicates that an appropriate amount of TAPB-DMTP-COF can form an effective heterojunction with ZnIn2S4, promoting charge separation; while an excessive amount of TAPB-DMTP-COF will act as a recombination center for photogenerated carriers, while also hindering the absorption of visible light by ZnIn2S4, leading to a decrease in catalytic performance.

[0078] The test results of Examples 1, 5, and 6 show that the catalytic performance is optimal when the oil bath reaction time is 2 h. As the reaction time is extended to 2.5 h and 3 h, the CH4 precipitation rate gradually decreases. This is because excessively long reaction times lead to excessive growth and aggregation of ZnIn2S4 nanosheets, increased shell thickness, longer migration distance of photogenerated carriers, and increased recombination probability, thereby reducing catalytic activity.

[0079] The test results of Comparative Examples 3-7 show that the CH4 precipitation rate is significantly reduced and almost negligible when ruthenium chloride hexahydrate (photosensitizer) or triethanolamine (sacrificial agent) is not added. This proves that the photosensitizer and sacrificial agent are essential components of this reaction system. Furthermore, no CH4 was detected when CO2 was not introduced, the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst prepared in Example 1 was not added, or the test was conducted in a dark environment. This indicates that the carbon element in the CH4 product originates from CO2 in the reaction system, rather than from the catalyst or other organic impurities, and that the generation of CH4 is a light-driven CO2 reduction reaction.

[0080] The test results of Comparative Example 8 show that when the oil bath temperature increases from 95℃ to 100℃, the CH4 precipitation rate increases from 59.3 µmol g / L. -1 h -1 It dropped sharply to 10.3 µmol g. -1 h -1 The reaction temperature affects the growth rate of ZnIn2S4. Higher temperatures accelerate the growth of ZnIn2S4 and result in a tighter coating between ZnIn2S4 and TAPB-DMTP-COF, thus increasing the rate of CH4 formation. However, excessively high temperatures lead to overgrowth and localized aggregation of the ZnIn2S4 shell, disrupting the tight core-shell interface between TAPB-DMTP-COF and ZnIn2S4, significantly weakening the charge separation and transport capabilities of the heterojunction. Simultaneously, excessively high temperatures increase the crystallinity of the generated ZnIn2S4, reducing the number of sulfur vacancy active sites on the ZnIn2S4 surface, making the heterojunction prone to failure and hindering CO2 adsorption and activation. During photocatalytic CO2 reduction performance testing, the failure of the heterojunction makes it easier for photogenerated electrons to undergo side reactions and compete for energy, ultimately leading to a sharp decrease in the rate of CH4 formation from the photocatalytic reduction of CO2. The temperature range of 95℃ to 100℃ corresponds precisely to the range in which the growth rate and crystallinity of ZnIn2S4 increase dramatically, which is why the precipitation rate of CH4 decreases sharply.

[0081] Test Example 2 The photocatalysts prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to photoelectrochemical tests: the results of transient photocurrent experiments and electrochemical impedance spectroscopy are shown in the figure. Figure 3-4 .

[0082] For transient photocurrent and electrochemical impedance spectroscopy (EIS) measurements: a standard three-electrode configuration was used, with 0.5 M Na₂SO₄ (pH=6.8) solution as the electrolyte, a fluorinated tin oxide (FTO) substrate coated with the catalyst as the working electrode, Ag / AgCl as the reference electrode, and a Pt sheet as the counter electrode. A 300 W xenon lamp was used as the light source. The working electrode was prepared as follows: 10 mg of catalyst was dispersed in a mixed solution of 4 mL water, 3 mL ethanol, and 3 mL isopropanol. 150 μL of the resulting suspension was drop-coated onto a clean FTO glass plate. The photocurrent was measured at 1.20 V vs. RHE, and the impedance spectroscopy was performed at 1.20 V vs. RHE at frequencies from 100 K to 0.1 Hz.

[0083] Figure 3 Photocurrent density curves are shown, with the photocurrent density of Example 1 being significantly higher than that of Comparative Examples 1 and 2, indicating higher light energy capture and carrier utilization efficiency. Meanwhile, as... Figure 4 The TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst prepared in Example 1 showed the smallest curve radius, indicating its lowest carrier transfer resistance. These results collectively demonstrate that the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst possesses optimal photoelectrochemical performance, enabling more efficient separation, transport, and utilization of photogenerated carriers.

[0084] Test Example 3 To evaluate the photogenerated carrier separation capabilities of the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst prepared in Example 1, the TAPB-DMTP-COF core prepared in Comparative Example 1, and the ZnIn2S4 photocatalyst prepared in Comparative Example 2, fluorescence lifetime analysis was performed, and time-resolved fluorescence spectra were obtained, as shown below. Figure 5 As shown, the fluorescence lifetimes of TAPB-DMTP-COF and ZnIn2S4 are 0.36 ns and 0.66 ns, respectively. Notably, when TAPB-DMTP-COF and ZnIn2S4 are combined to form a core-shell heterostructure, its fluorescence lifetime is significantly extended, reaching 1.67 ns. The fluorescence lifetimes of TAPB-DMTP-COF@ZnIn2S4 are 4.6 times and 2.5 times that of TAPB-DMTP-COF and ZnIn2S4, respectively.

[0085] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing the production of methane from carbon dioxide, characterized in that, The composite photocatalyst has a core-shell structure, with TAPB-DMTP-COF as the core and ZnIn2S4 as the shell. The ZnIn2S4 shell is grown in situ on the surface of the TAPB-DMTP-COF core and coats the surface of the TAPB-DMTP-COF core. The composite photocatalyst has a CH4 yield greater than 10.0 µmol g. -1 h -1 .

2. The composite photocatalyst according to claim 1, characterized in that, The mass fraction of the TAPB-DMTP-COF core in the composite photocatalyst is 0.1%~1.0wt%.

3. The composite photocatalyst according to claim 1, characterized in that, The average particle size of the TAPB-DMTP-COF core is 400-490 nm, and the average thickness of the ZnIn2S4 shell is 300-335 nm.

4. The composite photocatalyst according to claim 1, characterized in that, The CO2 chemisorption capacity of the composite photocatalyst is not less than 19 μmol g. -1 ; and / or The composite photocatalyst exhibits a selectivity of no less than 99.0% for CH4.

5. The composite photocatalyst according to claim 1, characterized in that, The composite photocatalyst exhibits a redshift of the absorption edge to 790-810 nm in the UV-Vis diffuse reflectance spectrum.

6. The method for preparing the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst for catalyzing the production of methane from carbon dioxide according to any one of claims 1-5, characterized in that, Including the following steps: (1) Preparation of TAPB-DMTP-COF kernel; (2) The TAPB-DMTP-COF core is dispersed in a mixed solvent of glycerol and deionized water to obtain a mixed solution; (3) Add zinc acetate dihydrate, indium chloride tetrahydrate and thioacetamide to the mixture in step (2); (4) Heating causes ZnIn2S4 to grow in situ and coat the surface of the TAPB-DMTP-COF core. The composite photocatalyst is obtained by separation, washing and drying.

7. The preparation method according to claim 6, characterized in that, In step (1), the preparation method of the TAPB-DMTP-COF core is as follows: S1: Dissolve 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxytetraphenyldialdehyde in acetonitrile, add acetic acid solution, stir for 2-10 min to obtain a suspension, and let the suspension stand at room temperature for 72 h; S2: Separate the suspension from the reaction in step S1 to obtain a solid, and wash and dry the solid to obtain the final product.

8. The method for preparing the composite photocatalyst according to claim 6, characterized in that, The heating temperature in step (4) is 95℃, and the reaction time is 2-3.5h; The volume ratio of glycerol to deionized water in step (2) is 1:(2-4).

9. A method for photocatalytic CO2 to CH4 production, characterized in that, Using the TAPB-DMTP-COF@ZnIn2S4 composite photocatalyst as described in any one of claims 1-5 as the photocatalyst, triethanolamine as the sacrificial agent, and ruthenium chloride hexahydrate as the photosensitizer, the catalytic reaction is carried out under visible light with λ≥420nm.

10. The application of the composite photocatalyst according to any one of claims 1-5 or the composite photocatalyst obtained by the preparation method according to any one of claims 6-8 in the photocatalytic production of CH4 from CO2.

Citation Information

Patent Citations

  • COF-ZnIn2S4 photocatalytic material with hollow core-shell structure as well as preparation method and application of COF-ZnIn2S4 photocatalytic material

    CN118904396A